2023
DOI: 10.24911/sjp.106-1603179359
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and management outcome of paediatrics burn in a general surgical department: experience from a secondary referral hospital

Abstract: Burns are considered the fourth most common type of traumatic injury worldwide with significant morbidity and mortality. The aim of this study is to disclose the incidence, etiological factors, treatment, and outcome of pediatric burns in Sudan. This is a retrospective hospital-based study, conducted during 2016- 2019. Patients who presented with burn injuries, managed in the hospital were included in the study. Flowchart sheets were used to collect the data. Then it was entered and analyzed using SPSS version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Notably, Olatain et al reported an 11% mortality rate, while Yiğit et al documented a 1.45% rate in their case series. Additionally, a retrospective study conducted in Sudan, focusing on hospital-based data, revealed burns as the fourth most common traumatic injury type, with a mortality rate of 5.9% (Bakhiet, 2023). In South Africa, a retrospective cohort study found an overall mortality rate of 4.4% for pediatric burns, with a higher mortality rate among transferred patients compared to directly admitted cases (Mashavave, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Olatain et al reported an 11% mortality rate, while Yiğit et al documented a 1.45% rate in their case series. Additionally, a retrospective study conducted in Sudan, focusing on hospital-based data, revealed burns as the fourth most common traumatic injury type, with a mortality rate of 5.9% (Bakhiet, 2023). In South Africa, a retrospective cohort study found an overall mortality rate of 4.4% for pediatric burns, with a higher mortality rate among transferred patients compared to directly admitted cases (Mashavave, 2020).…”
Section: Discussionmentioning
confidence: 99%